The integration between Romans and barbarians in the late Roman Empire - Silva, Semíramis Corsi (Romanitas - Revista de Estudos Grecolatinos, 2013)
Review of: FRIGHETTO, Renan. Antiguidade Tardia: Roma e as monarquias romano-bárbaras numa época de transformações. Séculos II-VIII. Curitiba: Juruá, 2012. 226 p.
Keywords: Late Antiquity; Classical Culture; German Culture